Wave-absorbing prepreg as well as preparation method and application thereof
In the preparation of the absorbing prepreg, the wave-transmissive resin is first combined with the fiber fabric and then with the absorbing adhesive film, the problem of random arrangement of absorbing agents caused by the flow of the absorbing resin is solved, and the absorption performance and process reliability are improved.
Patent Information
- Application Number
- CN202411972800.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
During the recombination process, the absorbents are randomly arranged due to the flow of the absorbent resin during the recombination process, which reduces the absorbing performance of the material.
First, the wave-transmissive resin film is combined with the fiber fabric to make the resin fill the fabric voids, and then the wave-absorbing film is combined to ensure the orientation and arrangement of the absorbent agent.
The absorbing performance and process reliability of the absorbing prepreg are improved, and the problem of disorderly orientation of the absorbent is avoided.
Smart Images

Figure CN119773341A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a wave absorbing prepreg and a preparation method and application thereof. Background Art
[0002] Absorbing materials are materials that convert electromagnetic wave energy into heat or other forms of energy dissipation to absorb and attenuate incident electromagnetic waves. Absorbing materials have been widely used in many fields, such as electromagnetic interference protection in the communication field and electromagnetic protection for the human body. Resin-based absorbing materials have become one of the important materials for stealth applications in the aerospace field due to their simple process, strong designability, and large-area integral molding.
[0003] The performance of absorbing materials is related to many factors, including the type of absorber, such as magnetic absorber, carbon absorber, alloy powder, etc. The performance of absorbing materials is also related to the morphology of the absorber, such as spherical absorber, sheet absorber, rod absorber. In addition, the performance of absorbing materials is also related to the dispersion state of the absorber in the system, such as dispersion uniformity and the degree of arrangement of the absorber in the system. Generally, the orientation of sheet absorbers in the system is conducive to improving the overall magnetic loss of the material.
[0004] Absorbing prepreg is a kind of absorbing material that can be integrated with structural materials. Compared with conventional coating materials (molded by spraying process), the integrated co-curing process of absorbing prepreg is simpler and more efficient. The preparation method of absorbing prepreg is usually prepared by hot melt method. The steps of this method are: first, use a coating machine to coat the absorbing resin into a film, and then composite the film and fiber fabric to obtain the absorbing prepreg, but its absorbing performance is limited. Summary of the invention
[0005] In order to further optimize the absorbing performance of the absorbing prepreg and enrich the selection space of the absorbing prepreg, the present invention provides an absorbing prepreg and a preparation method thereof. The method for preparing the absorbing prepreg provided by the present invention firstly composites a transparent resin film with a fiber fabric, so that the resin fills the gaps in the fabric to obtain a prepreg, and then composites the absorbing adhesive film with the prepreg to obtain an absorbing prepreg with an oriented absorbent, thereby solving the problem of random arrangement of the absorbent due to the flow of the absorbing resin during the composite process, thereby improving the absorbing performance of the absorbing prepreg.
[0006] As one aspect of the present invention, it relates to an absorbing prepreg, comprising two layers of absorbing adhesive films, two layers of transparent adhesive films and a layer of fiber fabric, which are the absorbing adhesive film layer, the transparent adhesive film layer, the fiber fabric layer, the transparent adhesive film layer and the absorbing adhesive film layer in sequence.
[0007] In a specific implementation manner, the fiber fabric is a mixed fabric of one of quartz fiber fabric, aramid fiber fabric and basalt fiber fabric or any combination thereof; the thickness of the fiber fabric is 0.05-0.1 mm.
[0008] As another aspect of the present invention, it relates to a method for preparing an absorbing prepreg, the method comprising:
[0009] a) mixing a base resin, a curing agent and an absorbent at 60 to 85° C. to obtain a roughly mixed absorbing resin; then finely mixing the roughly mixed absorbing resin at 60 to 85° C. to obtain a finely mixed absorbing resin;
[0010] b) mixing the base resin and the curing agent at 60-75° C. to obtain a coarse mixed resin; then refining and fine mixing the coarse mixed wave-transmitting resin at 65-75° C. to obtain a fine mixed wave-transmitting resin;
[0011] c) coating the finely mixed absorbing resin obtained in step a) on release paper at a coating temperature of 75° C. to 95° C. to obtain an absorbing adhesive film; coating the finely mixed transparent resin obtained in step b) on release paper at a coating temperature of 75° C. to 95° C. to obtain a transparent adhesive film;
[0012] d) Compounding the fiber fabric between two layers of the wave-transmitting adhesive film at a compounding temperature of 65-85° C. to obtain a primary pre-impregnated fabric, and then curing the primary pre-impregnated fabric at 70-90° C. to obtain a pre-impregnated fabric.
[0013] e) Compounding the preimpregnated fabric between two layers of the absorbing adhesive film at a compounding temperature of 65° C. to 80° C. to obtain an absorbing prepreg, wherein the absorbing prepreg comprises, from top to bottom, the absorbing adhesive film, the transparent adhesive film, the fiber fabric, the transparent adhesive film and the absorbing adhesive film.
[0014] In a specific implementation manner, in step a), the mass ratio of the absorbent, the matrix resin and the curing agent is 5-13.5:3-4:0-1.
[0015] In a specific embodiment, in step b), the mass ratio of the base resin to the curing agent is 3 to 4:1.
[0016] In a specific implementation manner, the absorbent is one of flaky carbonyl iron, flaky sendustine, flaky iron silicon chromium, flaky iron silicon nickel and chopped carbon fiber or any combination thereof, and the particle size of the absorbent is 5 to 100 microns.
[0017] In a specific embodiment, the base resin is one of epoxy resin, cyanate resin, bismaleimide resin and phenolic resin or any combination thereof; the curing agent is one of dicyandiamide, diallyl bisphenol A, phthalic anhydride, p-phenylenediamine and p-toluenesulfonic acid or any combination thereof.
[0018] In a specific implementation manner, the fiber fabric is a mixed fabric of one of quartz fiber fabric, aramid fiber fabric and basalt fiber fabric or any combination thereof, and the thickness of the fiber fabric is 0.05-0.1 mm.
[0019] In a specific implementation manner, the thickness of the wave-transmitting adhesive film is 40% to 60% of the thickness of the fiber fabric; the thickness of the wave-absorbing adhesive film is 120% to 166.7% of the thickness of the fiber fabric.
[0020] As another aspect of the present invention, it relates to the application of the above-mentioned absorbing prepreg in absorbing equipment.
[0021] Compared with the prior art, the present invention has at least the following beneficial effects:
[0022] (1) The method for preparing the absorbing prepreg provided by the present invention firstly composites the wave-transmitting adhesive film with the fiber fabric and then composites it with the absorbing adhesive film, thereby improving the bonding force between the resin and the fiber and improving the process reliability of the absorbing prepreg;
[0023] (2) The method for preparing the absorbing prepreg provided by the present invention avoids disordered orientation of the absorber caused by the flow of the absorbing resin between the fiber gaps, thereby improving the absorbing performance of the absorbing prepreg. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The figure is a schematic diagram of the process flow of preparing the microwave absorbing prepreg according to the embodiment of the present invention;
[0025] Figure 2 This is a cross-sectional microscopic morphology of the cyanate ester absorbing composite prepared in Example 3;
[0026] Figure 3 This is a cross-sectional microscopic morphology of the cyanate ester absorbing composite prepared in Comparative Example 3;
[0027] In the picture, the relatively large continuous black area is the fabric, marked as 1; the white area is the absorbent, marked as 2; the relatively scattered black area existing in the gaps of the absorbent is the resin, marked as 31 for fabric, 2 for absorbent, and 3 for resin. DETAILED DESCRIPTION
[0028] The inventors prepared a microwave-absorbing epoxy resin with reference to CN 113801437 B, and prepared a microwave-absorbing cyanate resin and a microwave-absorbing cyanate resin composite with reference to CN 113755013 B. However, during the preparation process, when the microwave-absorbing adhesive film and the fiber fabric are compounded, the resin will flow and fill the gaps in the fiber fabric, and the absorbent will also be randomly arranged with the flow of the resin, thereby reducing the microwave-absorbing effect.
[0029] With reference to CN 118744542 A, the inventor prepared a low-frequency absorbing prepreg for the P and L bands, and adopted a secondary hot pressing method to improve the orientation of the absorbent. However, the secondary molding effect is affected by many factors such as temperature, speed, pressure and the fabric itself, and it cannot solve the problem of resin flowing into the gaps, so the effect is limited.
[0030] Since the above existing technologies cannot meet the expectations of the inventors, the present invention is made after further research and development. The method provided by the present invention prepares a microwave absorbing prepreg capable of maintaining the orientation arrangement of the absorbent.
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] Embodiment 1:
[0033] A microwave absorbing prepreg and a preparation method thereof, comprising the following steps:
[0034] S1. Prepare a finely mixed absorbing resin: add a mixed absorbent, bisphenol A epoxy resin E51 and dicyandiamide (curing agent) in a mass ratio of 8:3:1 into a three-roll mill, wherein the mixed absorbent is composed of sheet-like sendust with a particle size of 45 μm and short-cut carbon fiber of 5 μm in a mass ratio of 4:1; use a three-roll mill of model GS-100 to mix at 60°C for 30 minutes to obtain a rough mixed absorbing resin. Then use a double planetary mixer of model SXHJ-100 to open and finely mix the above-mentioned rough mixed absorbing resin to obtain a finely mixed absorbing resin: the temperature of the open and fine mixing is 60°C, the time of the open and fine mixing is 45 minutes, and the rotor speed of the open and fine mixing is 25rpm.
[0035] S2. Prepare finely mixed wave-transmitting resin: add bisphenol A epoxy resin E44 and dicyandiamide (curing agent) in a mass ratio of 3:1 into a three-roll mill, and mix them at 60°C for 30 minutes using a three-roll mill of model GS-100 to obtain a roughly mixed wave-transmitting resin. Then, use a double planetary mixer of model SXHJ-100 to mix the roughly mixed wave-transmitting resin to obtain a finely mixed wave-transmitting resin: the mixing temperature is 65°C, the mixing time is 30 minutes, and the rotor speed of the mixing is 40 rpm.
[0036] S3. Prepare adhesive film: Use a coating machine to coat the finely mixed absorbing resin obtained in step S1 on the release paper, the coating temperature is 75°C, the coating speed is 3m / min, and a 0.08mm thick absorbing adhesive film is obtained; use a coating machine to coat the finely mixed wave-transmitting resin obtained in step S2 on the release paper, the coating temperature is 75°C, the coating speed is 4m / min, and a 0.03mm thick wave-transmitting adhesive film is obtained.
[0037] S4. Preparation of preimpregnated fabric: Select 0.06mm aramid fiber plain fabric, use a composite machine, the composite temperature is 65°C, the composite speed is 3m / min, the aramid fiber plain fabric is composited between two layers of wave-transmitting adhesive film to obtain a primary preimpregnated fabric, and then keep the primary preimpregnated fabric at 70°C for 0.5h (curing) to obtain a preimpregnated fabric.
[0038] S5. Preparation of absorbing prepreg: Use a compounding machine with a compounding temperature of 65°C and a compounding speed of 3m / min to compound the prepreg fabric between two layers of absorbing adhesive films to obtain an absorbing prepreg composed of absorbing adhesive film, transparent adhesive film, aramid fiber plain fabric, transparent adhesive film and absorbing adhesive film from top to bottom. The process of preparing absorbing prepreg is as follows: Figure 1 .
[0039] The absorbing prepreg of this embodiment is used to prepare epoxy absorbing composites and perform performance tests:
[0040] Preparation of epoxy absorbing composites: The absorbing prepreg prepared in step S5 is used to prepare an epoxy absorbing composite according to the following autoclave curing procedure: 4 layers of absorbing prepreg are laid flat on a flat tooling mold, wherein polytetrafluoroethylene cloth is laid on the flat tooling mold, and then a vacuum bag is assembled, which includes, from top to bottom, a vacuum bag film, a breathable felt, an isolation film, a peelable cloth, 4 layers of absorbing prepreg, polytetrafluoroethylene cloth and a flat tooling mold, one end of the vacuum tube is inserted into the vacuum bag film and fixed with a sealing tape, and the sealing tape is used to seal along the edge of the vacuum bag film, and then a vacuum pump is connected to evacuate at room temperature with a vacuum degree of 0.085 MPa to form a preform. Subsequently, the preform was placed in an autoclave, pressurized to 0.6 MPa, heated to 130°C at a rate of 1°C / min, kept warm for 2 hours, and cooled to below 60°C at a cooling rate of 1.5°C / min. After the preform temperature dropped to room temperature, the vacuum bag, breathable felt, isolation film, peelable cloth and polytetrafluoroethylene cloth were removed to obtain an epoxy absorbing composite material formed by curing 4 layers of absorbing prepreg, and the average thickness of the epoxy absorbing composite material was 0.81 mm.
[0041] The epoxy absorbing composite material was processed into 500mm×500mm and 300mm×300mm flat plates. The vertical reflectivity of the samples at 1 to 18 GHz was tested using a 1 to 18 GHz bow method reflectivity test device. The test results are shown in Table 1.
[0042] It can be seen from Table 1 that the average reflectivity absorption peak of the epoxy absorbing composite material prepared in this embodiment is -1.65dB at 1-2GHz, -4.06dB at 2-4GHz, -7.39dB at 4-8GHz, -10.67dB at 8-12GHz, and -5.51dB at 12-18GHz.
[0043] Embodiment 2:
[0044] A microwave absorbing prepreg and a preparation method thereof, comprising the following steps:
[0045] S1. Prepare finely mixed absorbing resin: add absorbent, T-type bisphenol A (curing agent) in a mass ratio of 5:4:1 into a three-roll mill, wherein the absorbent is flaky iron silicon chromium with a particle size of 100 μm; use a three-roll mill of model GS-100 to mix at 70°C for 30 minutes to obtain a roughly mixed absorbing resin. Then use a double planetary mixer of model SXHJ-100 to open and finely mix the above-mentioned roughly mixed absorbing resin to obtain a finely mixed absorbing resin: the temperature of the open and fine mixing is 70°C, the time of the open and fine mixing is 30 minutes, and the rotor speed of the open and fine mixing is 15 rpm.
[0046] S2. Prepare finely mixed wave-transmitting resin: Add HVA-2 metaphenylene bismaleimide resin and paraphenylenediamine (curing agent) in a mass ratio of 4:1 into a three-roll mill, and mix them at 70°C for 40 minutes using a three-roll mill of model GS-100 to obtain a roughly mixed wave-transmitting resin. Then, use a double planetary mixer of model SXHJ-100 to mix the roughly mixed wave-transmitting resin to obtain a finely mixed wave-transmitting resin: the mixing temperature is 65°C, the mixing time is 30 minutes, and the rotor speed of the mixing is 35 rpm.
[0047] S3. Prepare adhesive film: Use a coating machine to coat the finely mixed absorbing resin obtained in step S1 on the release paper, the coating temperature is 80°C, the coating speed is 2m / min, and a 0.08mm thick absorbing adhesive film is obtained; use a coating machine to coat the finely mixed wave-transmitting resin obtained in step S2 on the release paper, the coating temperature is 80°C, the coating speed is 3m / min, and a 0.025mm thick wave-transmitting adhesive film is obtained.
[0048] S4. Preparation of preimpregnated fabric: select 0.05mm quartz fiber twill fabric, use a composite machine, the composite temperature is 70°C, the composite speed is 2m / min, the quartz fiber twill fabric is composited between two layers of wave-transmitting adhesive film to obtain a primary preimpregnated fabric, and then the primary preimpregnated fabric is maintained at 85°C for 0.5h (curing) to obtain a preimpregnated fabric.
[0049] S5. Preparation of absorbing prepreg: Use a compounding machine, with a compounding temperature of 70°C and a compounding speed of 2m / min, to compound the prepreg fabric between two layers of absorbing adhesive films, to obtain an absorbing prepreg composed of absorbing adhesive film, transparent adhesive film, quartz fiber twill fabric, transparent adhesive film and absorbing adhesive film from top to bottom. The process of preparing absorbing prepreg is as follows: Figure 1 .
[0050] The absorbing prepreg of this embodiment is used to prepare a double-male absorbing composite material and perform testing:
[0051] Preparation of BMI absorbing composites: The absorbing prepreg prepared in step S5 is used to prepare a BMI absorbing composite according to the following autoclave curing procedure: 4 layers of absorbing prepreg are laid flat on a flat tooling mold, wherein polytetrafluoroethylene cloth is laid on the flat tooling mold, and then a vacuum bag is assembled, which is composed of a vacuum bag film, a breathable felt, an isolation film, a peelable cloth, 4 layers of absorbing prepreg, polytetrafluoroethylene cloth and a flat tooling mold from top to bottom, one end of the vacuum tube is inserted into the vacuum bag film and fixed with a sealing tape, and the sealing tape is used to seal along the edge of the vacuum bag film, and then a vacuum pump is connected to evacuate at room temperature, and the vacuum degree is 0.085 MPa to form a preform. Subsequently, the preform was placed in an autoclave, pressurized to 0.6 MPa, heated to 180°C at a rate of 1°C / min, kept warm for 1 hour, and then heated to 210°C and kept warm for 2 hours. The pressure was maintained and the preform was cooled to below 60°C at a cooling rate of 1.5°C / min. After the preform temperature dropped to room temperature, the vacuum bag, breathable felt, isolation film, peelable cloth and polytetrafluoroethylene cloth were removed to obtain a bismaleimide absorbing composite material cured from 4 layers of absorbing prepreg. The average thickness of the bismaleimide absorbing composite material was 0.75 mm.
[0052] The above-mentioned double-male absorber composite material was processed into 500mm×500mm and 300mm×300mm flat plates. The vertical reflectivity of the samples at 1 to 18 GHz was tested using a 1 to 18 GHz bow method reflectivity test equipment. The test results are shown in Table 1.
[0053] The average reflectivity absorption peak of the BMI absorbing composite material prepared in this embodiment is -1.38dB at 1-2GHz, -3.96dB at 2-4GHz, -6.89dB at 4-8GHz, -9.75dB at 8-12GHz, and -5.42dB at 12-18GHz. The results are shown in Table 1.
[0054] Embodiment 3:
[0055] A microwave absorbing prepreg and a preparation method thereof, comprising the following steps:
[0056] S1. Prepare finely mixed absorbing resin: add absorbent, bisphenol S cyanate resin and phthalic anhydride (curing agent) in a mass ratio of 27:7:2 into a three-roll mill, wherein the absorbent is flaky carbonyl iron with a particle size of 20 μm; use a three-roll mill of model GS-100 to mix at 70°C for 30 minutes to obtain a roughly mixed absorbing resin. Then use a double planetary mixer of model SXHJ-100 to open and finely mix the above-mentioned roughly mixed absorbing resin to obtain a finely mixed absorbing resin: the temperature of the open and fine mixing is 70°C, the time of the open and fine mixing is 30 minutes, and the rotor speed of the open and fine mixing is 25 rpm.
[0057] S2. Prepare finely mixed wave-transmitting resin: add bisphenol S cyanate resin and phthalic anhydride (curing agent) in a mass ratio of 7:2 into a three-roll mill, and mix them at 70°C for 30 minutes using a three-roll mill of model GS-100 to obtain a roughly mixed wave-transmitting resin. Then, use a double planetary mixer of model SXHJ-100 to mix the roughly mixed wave-transmitting resin to obtain a finely mixed wave-transmitting resin: the mixing temperature is 70°C, the mixing time is 30 minutes, and the rotor speed of the mixing is 35 rpm.
[0058] S3. Prepare adhesive film: Use a coating machine to coat the finely mixed absorbing resin obtained in step S1 on the release paper, the coating temperature is 85°C, the coating speed is 3m / min, and a 0.12mm thick absorbing adhesive film is obtained; use a coating machine to coat the finely mixed wave-transmitting resin obtained in step S2 on the release paper, the coating temperature is 85°C, the coating speed is 4m / min, and a 0.05mm thick wave-transmitting adhesive film is obtained.
[0059] S4. Preparation of preimpregnated fabric: select quartz aramid blended fiber plain fabric with a thickness of 0.1 mm, use a composite machine, the composite temperature is 75 ° C, the composite speed is 3 m / min, the quartz aramid blended fiber plain fabric is composited between two layers of wave-transmitting adhesive film to obtain a primary preimpregnated fabric, and then keep the primary preimpregnated fabric at 80 ° C for 0.5 h (curing) to obtain a preimpregnated fabric.
[0060] S5. Preparation of absorbing prepreg: Use a compounding machine with a compounding temperature of 75°C and a compounding speed of 3m / min to compound the prepreg fabric between two layers of absorbing adhesive films to obtain an absorbing prepreg composed of absorbing adhesive film, transparent adhesive film, quartz aramid mixed fiber plain fabric, transparent adhesive film and absorbing adhesive film from top to bottom. The process of preparing absorbing prepreg is as follows: Figure 1 .
[0061] The cyanate ester absorbing composite was prepared using the absorbing prepreg of this example and tested:
[0062] Preparation of cyanate absorbing composites: The absorbing prepreg prepared in step S5 is used to prepare a cyanate absorbing composite according to the following autoclave curing procedure: 4 layers of absorbing prepreg are laid flat on a flat tooling mold, wherein polytetrafluoroethylene cloth is laid on the flat tooling mold, and then a vacuum bag is assembled, which includes, from top to bottom, a vacuum bag film, a breathable felt, an isolation film, a peelable cloth, 4 layers of absorbing prepreg, polytetrafluoroethylene cloth and a flat tooling mold, one end of the vacuum tube is inserted into the vacuum bag film and fixed with a sealing tape, and the sealing tape is used to seal along the edge of the vacuum bag film, and then a vacuum pump is connected to evacuate at room temperature with a vacuum degree of 0.085 MPa to form a preform. Subsequently, the preform was placed in an autoclave, pressurized to 0.6 MPa, heated to 100°C at a rate of 1°C / min, kept warm for 1 hour, then heated to 150°C and kept warm for 2 hours, then heated to 200°C and kept warm for 2 hours, the pressure was maintained, and the preform was cooled to below 60°C at a cooling rate of 1.5°C / min, and then taken out of the autoclave. After the temperature of the preform dropped to room temperature, the vacuum bag, breathable felt, isolation film, peelable cloth and polytetrafluoroethylene cloth were removed to obtain a cyanate absorbing composite material formed by curing 4 layers of absorbing prepreg, and the total thickness of the cyanate absorbing composite material was 1.22 mm.
[0063] The cross-sectional microstructure of the cyanate ester absorbing composite prepared in this embodiment is as follows: Figure 2 As shown, ① is fabric, ② is absorbent, and ③ is resin. It can be seen that the absorbent maintains an oriented arrangement in the transverse direction of the figure.
[0064] The above cyanate ester absorbing composite material was processed into 500mm×500mm and 300mm×300mm flat plates. The vertical reflectivity of the sample at 1 to 18 GHz was tested using a 1 to 18 GHz bow method reflectivity test device. The test results are shown in Table 1.
[0065] The cyanate absorbing composite prepared in this embodiment has an average reflectivity absorption peak of -1.45 dB at 1-2 GHz, an average reflectivity absorption peak of -3.22 dB at 2-4 GHz, an average reflectivity absorption peak of -8.92 dB at 4-8 GHz, an average reflectivity absorption peak of -15.1 dB at 8-12 GHz, and an average reflectivity absorption peak of -7.84 dB at 12-18 GHz. The results are shown in Table 1.
[0066] Embodiment 4:
[0067] A microwave absorbing prepreg and a preparation method thereof, comprising the following steps:
[0068] S1. Prepare a finely mixed absorbing resin: add an absorbent and a magnesium phenolic resin in a mass ratio of 10:4 into a three-roll mill, wherein the absorbent is a sheet of iron silicon nickel with a particle size of 50 μm; use a three-roll mill of model GS-100 to mix at 85°C for 30 minutes to obtain a roughly mixed absorbing resin. Then use a double planetary mixer of model SXHJ-100 to open and finely mix the above-mentioned roughly mixed absorbing resin to obtain a finely mixed absorbing resin: the temperature of the open and fine mixing is 85°C, the time of the open and fine mixing is 30 minutes, and the rotor speed of the open and fine mixing is 20rpm.
[0069] S2. Prepare finely mixed wave-transmitting resin: add barium phenolic resin and p-toluenesulfonic acid (curing agent) in a mass ratio of 3:1 into a three-roll mill, and mix them at 75°C for 30 minutes using a three-roll mill of model GS-100 to obtain a roughly mixed wave-transmitting resin. Then, use a double planetary mixer of model SXHJ-100 to mix the roughly mixed wave-transmitting resin to obtain a finely mixed wave-transmitting resin: the mixing temperature is 75°C, the mixing time is 30 minutes, and the rotor speed of the mixing is 35 rpm.
[0070] S3. Prepare adhesive film: Use a coating machine to coat the finely mixed absorbing resin obtained in step S1 on the release paper, the coating temperature is 90°C, the coating speed is 1 m / min, and a 0.15 mm thick absorbing adhesive film is obtained; use a coating machine to coat the finely mixed wave-transmitting resin obtained in step S2 on the release paper, the coating temperature is 90°C, the coating speed is 2 m / min, and a 0.05 mm thick wave-transmitting adhesive film is obtained.
[0071] S4. Preparation of preimpregnated fabric: Select 0.1 mm basalt fiber plain fabric, use a composite machine, the composite temperature is 75 ° C, the composite speed is 3 m / min, the basalt fiber plain fabric is composited between two layers of wave-transmitting adhesive film to obtain a primary preimpregnated fabric, and then keep the primary preimpregnated fabric at 85 ° C for 0.5 h (curing) to obtain a preimpregnated fabric.
[0072] S5. Preparation of absorbing prepreg: Use a compounding machine with a compounding temperature of 80°C and a compounding speed of 2m / min to compound the prepreg fabric between two layers of absorbing adhesive films to obtain an absorbing prepreg composed of absorbing adhesive film, transparent adhesive film, basalt fiber plain fabric, transparent adhesive film and absorbing adhesive film from top to bottom. The process of preparing absorbing prepreg is as follows: Figure 1 .
[0073] The phenolic absorbing composite was prepared using the absorbing prepreg of this embodiment and tested:
[0074] Preparation of phenolic absorbing composites: The absorbing prepreg prepared in step S5 is used to prepare a phenolic absorbing composite according to the following autoclave curing procedure: three layers of absorbing prepreg are laid flat on a flat tooling mold, wherein polytetrafluoroethylene cloth is laid on the flat tooling mold, and then a vacuum bag is assembled, which includes, from top to bottom, a vacuum bag film, a breathable felt, an isolation film, a peelable cloth, three layers of absorbing prepreg, polytetrafluoroethylene cloth and a flat tooling mold, one end of a vacuum tube is inserted into the vacuum bag film and fixed with a sealing tape, and the sealing tape is used to seal along the edge of the vacuum bag film, and then a vacuum pump is connected to evacuate at room temperature, and the vacuum degree is 0.085 MPa to form a preform. Subsequently, the preform was placed in an autoclave, pressurized to 0.6 MPa, heated to 130°C at a rate of 1°C / min, kept warm for 1 hour, and then heated to 180°C for 2 hours. The pressure was maintained and the preform was cooled to below 60°C at a cooling rate of 1.5°C / min. The preform was taken out of the autoclave, and after the temperature of the preform dropped to room temperature, the vacuum bag, breathable felt, isolation film, peelable cloth and polytetrafluoroethylene cloth were removed to obtain a phenolic absorbing composite material cured by 4 layers of absorbing prepreg. The total thickness of the phenolic absorbing composite material was 1.03 mm.
[0075] The above phenolic absorbing composite material was processed into 500mm×500mm and 300mm×300mm flat plates. The vertical reflectivity of the samples at 1 to 18 GHz was tested using a 1 to 18 GHz bow method reflectivity test device. The test results are shown in Table 1.
[0076] The phenolic absorbing composite material prepared in this embodiment has an average reflectivity absorption peak of -1.02dB at 1-2GHz, an average reflectivity absorption peak of -3.95dB at 2-4GHz, an average reflectivity absorption peak of -6.85dB at 4-8GHz, an average reflectivity absorption peak of -12.11dB at 8-12GHz, and an average reflectivity absorption peak of -5.76dB at 12-18GHz. The results are shown in Table 1.
[0077] Embodiment 5:
[0078] A microwave absorbing prepreg and a preparation method thereof, comprising the following steps:
[0079] S1. Prepare finely mixed absorbing resin: add absorbent, HVA-2 metaphenylene bismaleimide resin and p-phenylenediamine (curing agent) in a mass ratio of 8:4:1 into a three-roll mill, wherein the absorbent is a sheet of sendustine with a particle size of 50 μm; use a three-roll mill of model GS-100 to mix at 70°C for 30 minutes to obtain a roughly mixed absorbing resin. Then use a double planetary mixer of model SXHJ-100 to mix the roughly mixed absorbing resin to obtain a finely mixed absorbing resin: the mixing temperature is 70°C, the mixing time is 30 minutes, and the rotor speed of the mixing is 30 rpm.
[0080] S2. Prepare finely mixed wave-transmitting resin: Add T-type bismaleimide resin and diallyl bisphenol A (curing agent) in a mass ratio of 4:1 into a three-roll mill, and mix them at 75°C for 30 minutes using a three-roll mill of model GS-100 to obtain a roughly mixed wave-transmitting resin. Then, use a double planetary mixer of model SXHJ-100 to mix the roughly mixed wave-transmitting resin to obtain a finely mixed wave-transmitting resin: the mixing temperature is 75°C, the mixing time is 30 minutes, and the rotor speed of the mixing is 35 rpm.
[0081] S3. Prepare adhesive film: Use a coating machine to coat the finely mixed absorbing resin obtained in step S1 on the release paper, the coating temperature is 80°C, the coating speed is 3m / min, and a 0.1mm thick absorbing adhesive film is obtained; use a coating machine to coat the finely mixed wave-transmitting resin obtained in step S2 on the release paper, the coating temperature is 80°C, the coating speed is 4m / min, and a 0.036mm thick wave-transmitting adhesive film is obtained.
[0082] S4. Preparation of preimpregnated fabric: select 0.06mm quartz fiber twill fabric, use a composite machine, the composite temperature is 75°C, the composite speed is 3m / min, the quartz fiber twill fabric is composited between two layers of wave-transmitting adhesive film to obtain a primary preimpregnated fabric, and then the primary preimpregnated fabric is maintained at 90°C for 0.5h (curing) to obtain a preimpregnated fabric.
[0083] S5. Preparation of absorbing prepreg: Use a compounding machine, with a compounding temperature of 70°C and a compounding speed of 3m / min, to compound the prepreg fabric between two layers of absorbing adhesive films to obtain an absorbing prepreg composed of absorbing adhesive film, transparent adhesive film, quartz fiber twill fabric, transparent adhesive film and absorbing adhesive film from top to bottom. The process of preparing absorbing prepreg is as follows: Figure 1 .
[0084] The absorbing prepreg of this embodiment is used to prepare a double-male absorbing composite material and perform testing:
[0085] Preparation of BMI absorbing composites: The absorbing prepreg prepared in step S5 is used to prepare a BMI absorbing composite according to the following autoclave curing procedure: 4 layers of absorbing prepreg are laid flat on a flat tooling mold, wherein polytetrafluoroethylene cloth is laid on the flat tooling mold, and then a vacuum bag is assembled, which is composed of a vacuum bag film, a breathable felt, an isolation film, a peelable cloth, 4 layers of absorbing prepreg, polytetrafluoroethylene cloth and a flat tooling mold from top to bottom, one end of the vacuum tube is inserted into the vacuum bag film and fixed with a sealing tape, and the sealing tape is used to seal along the edge of the vacuum bag film, and then a vacuum pump is connected to evacuate at room temperature, and the vacuum degree is 0.085 MPa to form a preform. Subsequently, the preform was placed in an autoclave, pressurized to 0.6 MPa, heated to 180°C at a rate of 1°C / min, kept warm for 1 hour, and then heated to 210°C and kept warm for 2 hours. The pressure was maintained and the preform was cooled to below 60°C at a cooling rate of 1.5°C / min. After the preform temperature dropped to room temperature, the vacuum bag, breathable felt, isolation film, peelable cloth and polytetrafluoroethylene cloth were removed to obtain a bismaleimide absorbing composite material cured from 4 layers of absorbing prepreg. The total thickness of the bismaleimide absorbing composite material was 0.89 mm.
[0086] The above-mentioned double-male absorber composite material was processed into 500mm×500mm and 300mm×300mm flat plates. The vertical reflectivity of the samples at 1 to 18 GHz was tested using a 1 to 18 GHz bow method reflectivity test equipment. The test results are shown in Table 1.
[0087] The average reflectivity absorption peak of the BMI absorbing composite material prepared in this embodiment is -1.93dB at 1-2GHz, -4.84dB at 2-4GHz, -8.71dB at 4-8GHz, -8.19dB at 8-12GHz, and -9.66dB at 12-18GHz. The results are shown in Table 1.
[0088] Embodiment 6:
[0089] A microwave absorbing prepreg and a preparation method thereof, comprising the following steps:
[0090] S1. Prepare finely mixed absorbing resin: add absorbent, barium phenolic resin and p-toluenesulfonic acid (curing agent) absorbent in a mass ratio of 7:3:1 into a three-roll mill, wherein the absorbent is flaky iron silicon chromium with a particle size of 55 μm; use a three-roll mill of model GS-100 to mix at 75°C for 30 minutes to obtain a roughly mixed absorbing resin. Then use a double planetary mixer of model SXHJ-100 to open and finely mix the above-mentioned roughly mixed absorbing resin to obtain a finely mixed absorbing resin: the temperature of the open and fine mixing is 75°C, the time of the open and fine mixing is 30 minutes, and the rotor speed of the open and fine mixing is 15 rpm.
[0091] S2. Prepare finely mixed wave-transmitting resin: add barium phenolic resin and p-toluenesulfonic acid (curing agent) in a mass ratio of 3:1 into a three-roll mill, and mix them at 75°C for 30 minutes using a three-roll mill of model GS-100 to obtain a roughly mixed wave-transmitting resin. Then, use a double planetary mixer of model SXHJ-100 to mix the roughly mixed wave-transmitting resin to obtain a finely mixed wave-transmitting resin: the mixing temperature is 75°C, the mixing time is 30 minutes, and the rotor speed of the mixing is 30 rpm.
[0092] S3. Prepare adhesive film: Use a coating machine to coat the finely mixed absorbing resin obtained in step S1 on the release paper, the coating temperature is 95°C, the coating speed is 1 m / min, and a 0.1 mm thick absorbing adhesive film is obtained; use a coating machine to coat the finely mixed wave-transmitting resin obtained in step S2 on the release paper, the coating temperature is 95°C, the coating speed is 2 m / min, and a 0.032 mm thick wave-transmitting adhesive film is obtained.
[0093] S4. Preparation of preimpregnated fabric: Select 0.08 mm aramid fiber forging fabric, use a composite machine, the composite temperature is 85 ° C, the composite speed is 2 m / min, the aramid fiber forging fabric is composited between two layers of wave-transmitting adhesive film to obtain a primary preimpregnated fabric, and then keep the primary preimpregnated fabric at 90 ° C for 0.5 h (curing) to obtain a preimpregnated fabric.
[0094] S5. Preparation of absorbing prepreg: Use a compounding machine, with a compounding temperature of 80°C and a compounding speed of 2m / min, to compound the prepreg fabric between two layers of absorbing adhesive films to obtain an absorbing prepreg composed of absorbing adhesive film, transparent adhesive film, aramid fiber forging fabric, transparent adhesive film and absorbing adhesive film from top to bottom. The process of preparing absorbing prepreg is as follows: Figure 1 .
[0095] The phenolic absorbing composite was prepared using the absorbing prepreg of this embodiment and tested:
[0096] Preparation of phenolic absorbing composites: The absorbing prepreg prepared in step S5 is used to prepare a phenolic absorbing composite according to the following autoclave curing procedure: 4 layers of absorbing prepreg are laid flat on a flat tooling mold, wherein polytetrafluoroethylene cloth is laid on the flat tooling mold, and then a vacuum bag is assembled, which includes, from top to bottom, a vacuum bag film, a breathable felt, an isolation film, a peelable cloth, 4 layers of absorbing prepreg, polytetrafluoroethylene cloth and a flat tooling mold, one end of a vacuum tube is inserted into the vacuum bag film and fixed with a sealing tape, and the sealing tape is used to seal along the edge of the vacuum bag film, and then a vacuum pump is connected to evacuate at room temperature, and the vacuum degree is 0.085 MPa to form a preform. Subsequently, the preform was placed in an autoclave, pressurized to 0.6 MPa, heated to 130°C at a rate of 1°C / min, kept warm for 1 hour, and then heated to 180°C for 2 hours. The pressure was maintained and the preform was cooled to below 60°C at a cooling rate of 1.5°C / min. The preform was taken out of the autoclave, and after the temperature of the preform dropped to room temperature, the vacuum bag, breathable felt, isolation film, peelable cloth and polytetrafluoroethylene cloth were removed to obtain a phenolic absorbing composite material formed by curing 4 layers of absorbing prepreg. The total thickness of the phenolic absorbing composite material was 0.97 mm.
[0097] The above phenolic absorbing composite material was processed into 500mm×500mm and 300mm×300mm flat plates. The vertical reflectivity of the samples at 1 to 18 GHz was tested using a 1 to 18 GHz bow method reflectivity test device. The test results are shown in Table 1.
[0098] The phenolic absorbing composite material prepared in this embodiment has an average reflectivity absorption peak of -1.32 dB at 1-2 GHz, an average reflectivity absorption peak of -4.75 dB at 2-4 GHz, an average reflectivity absorption peak of -7.35 dB at 4-8 GHz, an average reflectivity absorption peak of -11.18 dB at 8-12 GHz, and an average reflectivity absorption peak of -5.01 dB at 12-18 GHz. The results are shown in Table 1.
[0099] The beneficial effects of the present invention are described below through comparative experiments:
[0100] Comparative Example 1:
[0101] S1. Preparation of finely mixed absorbing resin: the same as step S1 of Example 1.
[0102] S2. Prepare an absorbing film: Use a coating machine to coat the finely mixed absorbing resin obtained in step S1 on a release paper to obtain an absorbing film, wherein the coating temperature is 75° C., the coating speed is 3 m / min, and the thickness of the absorbing film is 0.09 mm.
[0103] S3. Preparation of absorbing prepreg: Select 0.06 mm aramid fiber plain fabric, use a composite machine, composite temperature of 65 ° C, composite speed of 3 m / min, composite the aramid fiber fabric between two layers of absorbing film to obtain absorbing prepreg.
[0104] The absorbing prepreg of this comparative example was used to prepare the epoxy absorbing composite material and perform the test:
[0105] Preparation of epoxy absorbing composites: The absorbing prepreg prepared in step S3 is used to prepare epoxy absorbing composites according to the following autoclave curing procedure: 4 layers of absorbing prepreg are laid flat on a flat tooling mold, wherein polytetrafluoroethylene cloth is laid on the flat tooling mold, and then a vacuum bag is assembled, which includes, from top to bottom, a vacuum bag film, a breathable felt, an isolation film, a peelable cloth, 4 layers of absorbing prepreg, polytetrafluoroethylene cloth and a flat tooling mold, one end of the vacuum tube is inserted into the vacuum bag film and fixed with a sealing tape, and the sealing tape is used to seal along the edge of the vacuum bag film, and then a vacuum pump is connected to evacuate at room temperature with a vacuum degree of 0.085 MPa to form a preform. The preform was then placed in an autoclave, pressurized to 0.6 MPa, heated to 130°C at a rate of 1°C / min, kept warm for 1 hour to maintain the pressure, cooled to below 60°C at a cooling rate of 1.5°C / min, and taken out of the autoclave. After the temperature of the preform dropped to room temperature, the vacuum bag, breathable felt, isolation film, peelable cloth and polytetrafluoroethylene cloth were removed to obtain an epoxy absorbing composite material consisting of 4 layers of absorbing prepreg cured.
[0106] The epoxy absorbing composite material was processed into 500mm×500mm and 300mm×300mm flat plates. The vertical reflectivity of the samples at 1 to 18 GHz was tested using a 1 to 18 GHz bow method reflectivity test device. The test results are shown in Table 1.
[0107] The epoxy absorbing composite material prepared in this comparative example has an average reflectivity absorption peak of -0.85 dB at 1-2 GHz, an average reflectivity absorption peak of -2.40 dB at 2-4 GHz, an average reflectivity absorption peak of -6.63 dB at 4-8 GHz, an average reflectivity absorption peak of -8.79 dB at 8-12 GHz, and an average reflectivity absorption peak of -4.30 dB at 12-18 GHz. The total thickness of the epoxy absorbing composite material is 0.81 mm. The results are shown in Table 1.
[0108] Comparative Example 2:
[0109] S1. Preparation of finely mixed absorbing resin: the same as step S1 of Example 2.
[0110] S2. Prepare an absorbing film: Use a coating machine to coat the finely mixed absorbing resin obtained in step S1 on a release paper to obtain an absorbing film, wherein the coating temperature is 80° C., the coating speed is 2 m / min, and the thickness of the absorbing film is 0.09 mm.
[0111] S3. Preparation of absorbing prepreg: Select 0.05 mm quartz fiber twill fabric, use a composite machine, composite temperature of 70 ° C, composite speed of 2 m / min, composite the quartz fiber twill fabric between two layers of absorbing film to obtain absorbing prepreg.
[0112] The absorbing prepreg of this comparative example was used to prepare a double-male absorbing composite material and tested:
[0113] Preparation of BMI absorbing composites: The absorbing prepreg prepared in step S3 is used to prepare a BMI absorbing composite according to the following autoclave curing procedure: 4 layers of absorbing prepreg are laid flat on a flat tooling mold, wherein polytetrafluoroethylene cloth is laid on the flat tooling mold, and then a vacuum bag is assembled, which includes, from top to bottom, a vacuum bag film, a breathable felt, an isolation film, a peelable cloth, 4 layers of absorbing prepreg, polytetrafluoroethylene cloth and a flat tooling mold, one end of the vacuum tube is inserted into the vacuum bag film and fixed with a sealing tape, and the sealing tape is used to seal along the edge of the vacuum bag film, and then a vacuum pump is connected to evacuate at room temperature with a vacuum degree of 0.085 MPa to form a preform. Subsequently, the preform was placed in an autoclave, pressurized to 0.6 MPa, heated to 180°C at a rate of 1°C / min, kept warm for 1 hour, and then heated to 210°C and kept warm for 2 hours. The pressure was maintained and the preform was cooled to below 60°C at a cooling rate of 1.5°C / min. After the preform temperature dropped to room temperature, the vacuum bag, breathable felt, isolation film, peelable cloth and polytetrafluoroethylene cloth were removed to obtain a BMF absorbing composite material cured from 4 layers of absorbing prepreg.
[0114] The above-mentioned double-male absorber composite material was processed into 500mm×500mm and 300mm×300mm flat plates. The vertical reflectivity of the samples at 1 to 18 GHz was tested using a 1 to 18 GHz bow method reflectivity test equipment. The test results are shown in Table 1.
[0115] The average reflectivity absorption peak of the bismaleimide absorbing composite material prepared in this comparative example is -0.97dB at 1-2GHz, -2.25dB at 2-4GHz, -6.12dB at 4-8GHz, -7.86dB at 8-12GHz, and -3.42dB at 12-18GHz. The total thickness of the bismaleimide absorbing composite material is 0.75mm. The results are shown in Table 1.
[0116] Comparative Example 3:
[0117] S1. Preparation of finely mixed absorbing resin: the same as step S1 of Example 3.
[0118] S2. Prepare an absorbing film: Use a coating machine to coat the finely mixed absorbing resin obtained in step S1 on a release paper to obtain an absorbing film, wherein the coating temperature is 85° C., the coating speed is 3 m / min, and the thickness of the absorbing film is 0.13 mm.
[0119] S3. Preparation of absorbing prepreg: Select 0.1 mm quartz aramid mixed fiber plain fabric, use a composite machine, composite temperature of 75 ° C, composite speed of 3m / min, composite the quartz aramid mixed fiber plain fabric between two layers of absorbing film to obtain absorbing prepreg.
[0120] The absorbing prepreg of this comparative example was used to prepare the epoxy absorbing composite material and perform the test:
[0121] Preparation of cyanate absorbing composites: The absorbing prepreg prepared in step S3 is used to prepare a cyanate absorbing composite according to the following autoclave curing procedure: 4 layers of absorbing prepreg are laid flat on a flat tooling mold, wherein polytetrafluoroethylene cloth is laid on the flat tooling mold, and then a vacuum bag is assembled, which includes, from top to bottom, a vacuum bag film, a breathable felt, an isolation film, a peelable cloth, 4 layers of absorbing prepreg, polytetrafluoroethylene cloth and a flat tooling mold, one end of the vacuum tube is inserted into the vacuum bag film and fixed with a sealing tape, and the sealing tape is used to seal along the edge of the vacuum bag film, and then a vacuum pump is connected to evacuate at room temperature with a vacuum degree of 0.085 MPa to form a preform. Subsequently, the preform was placed in an autoclave, pressurized to 0.6 MPa, heated to 100°C at a rate of 1°C / min, kept warm for 1 hour, then heated to 150°C and kept warm for 2 hours, then heated to 200°C and kept warm for 2 hours, the pressure was maintained, and the preform was cooled to below 60°C at a cooling rate of 1.5°C / min, and then taken out of the autoclave. After the temperature of the preform dropped to room temperature, the vacuum bag, breathable felt, isolation film, peelable cloth and polytetrafluoroethylene cloth were removed to obtain a cyanate absorbing composite material formed by curing 4 layers of absorbing prepreg.
[0122] The cross-sectional microstructure of the cyanate absorbing composite prepared in this comparative example is as follows: Figure 3 As shown, ① is fabric, ② is absorbent, and ③ is resin. It can be seen that the absorbent is arranged in disorder in the figure.
[0123] The above cyanate ester absorbing composite material was processed into 500mm×500mm and 300mm×300mm flat plates. The vertical reflectivity of the sample at 1 to 18 GHz was tested using a 1 to 18 GHz bow method reflectivity test device. The test results are shown in Table 1.
[0124] The cyanate ester absorbing composite prepared in this comparative example has an average reflectivity absorption peak of -1.02 dB at 1-2 GHz, an average reflectivity absorption peak of -2.35 dB at 2-4 GHz, an average reflectivity absorption peak of -7.69 dB at 4-8 GHz, an average reflectivity absorption peak of -13.26 dB at 8-12 GHz, and an average reflectivity absorption peak of -6.33 dB at 12-18 GHz. The total thickness of the cyanate ester absorbing composite is 1.22 mm. The results are shown in Table 1.
[0125] Table 1 Performance comparison of Examples 1 to 6 and Comparative Examples 1 to 3
[0126]
[0127] By comparing the reflectivity of Example 1 and Comparative Example 1, the reflectivity of Example 2 and Comparative Example 2, and the reflectivity of Example 3 and Comparative Example 3 in Table 1, it can be seen that the reflectivity of the absorbing composite material prepared in the embodiment of the present invention is reduced in the frequency range of 1-18 GHz, that is, the absorbing performance is improved.
[0128] The methods for preparing the microwave absorbing prepregs in Examples 1-6 can be summarized as follows:
[0129] a) preparing a finely mixed absorbing resin: mixing a base resin, a curing agent and an absorbent at 60-85° C. to obtain a roughly mixed absorbing resin; then finely mixing the roughly mixed absorbing resin at 60-85° C. to obtain a finely mixed absorbing resin;
[0130] b) preparing a finely mixed wave-transmitting resin: mixing a base resin and a curing agent at 60-75° C. to obtain a roughly mixed resin; then finely mixing the roughly mixed wave-transmitting resin at 65-75° C. to obtain a finely mixed wave-transmitting resin;
[0131] c) preparing adhesive film: coating the finely mixed absorbing resin obtained in step a) on release paper at a coating temperature of 75°C to 95°C and a coating speed of 1 to 4 m / min to obtain an absorbing adhesive film; coating the finely mixed transparent resin obtained in step b) on release paper at a coating temperature of 75°C to 95°C and a coating speed of 1 to 4 m / min to obtain a transparent adhesive film;
[0132] d) Preparing preimpregnated fabric: Compounding the fiber fabric between two layers of wave-transmitting adhesive films at a compounding temperature of 65-85° C. and a compounding speed of 2-3 m / min to obtain a primary preimpregnated fabric, and then curing the primary preimpregnated fabric at 70-90° C. to obtain a preimpregnated fabric.
[0133] e) preparing a absorbing prepreg: compounding the preimpregnated fabric between two layers of absorbing adhesive films at a compounding temperature of 65°C to 80°C and a compounding speed of 2 to 3 m / min to obtain a absorbing prepreg, wherein the absorbing prepreg comprises, from top to bottom, the absorbing adhesive film, the transparent adhesive film, the fiber fabric, the transparent adhesive film and the absorbing adhesive film.
[0134] Wherein, in step a), the mass ratio of the absorbent, the matrix resin and the curing agent is 5-13.5:3-4:0-1;
[0135] In step b), the mass ratio of the base resin to the curing agent is 3 to 4:1;
[0136] The absorbent is one of flaky carbonyl iron, flaky iron silicon aluminum, flaky iron silicon chromium, flaky iron silicon nickel and chopped carbon fiber or any combination thereof; the particle size of the absorbent is 5 to 100 microns;
[0137] The base resin is one of epoxy resin, cyanate resin, bismaleimide resin and phenolic resin or any combination thereof; the curing agent is one of dicyandiamide, diallyl bisphenol A, phthalic anhydride, p-phenylenediamine and p-toluenesulfonic acid or any combination thereof;
[0138] In step d), the fiber fabric is a quartz fiber fabric, an aramid fiber fabric, a basalt fiber fabric, or a mixed fabric of any combination thereof; the thickness of the fiber fabric is 0.05 to 0.1 mm;
[0139] The thickness of the wave-transmitting adhesive film is 40% to 60% of the thickness of the fiber fabric;
[0140] The thickness of the wave-absorbing film is 120% to 166.7% of the thickness of the fiber fabric.
[0141] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A microwave absorbing prepreg, characterized in that: It comprises two layers of wave-absorbing adhesive films, two layers of wave-transmitting adhesive films and a layer of fiber fabric, which are the wave-absorbing adhesive film layer, the wave-transmitting adhesive film layer, the fiber fabric layer, the wave-transmitting adhesive film layer and the wave-absorbing adhesive film layer in sequence.
2. The microwave absorbing prepreg according to claim 1, characterized in that: The fiber fabric is a mixed fabric of one of quartz fiber fabric, aramid fiber fabric and basalt fiber fabric or any combination thereof.
3. A method for preparing a microwave absorbing prepreg, characterized in that: include: a) mixing a base resin, a curing agent and an absorbent at 60 to 85° C. to obtain a roughly mixed absorbing resin; then refining and fine mixing the roughly mixed absorbing resin at 60 to 85° C. to obtain a finely mixed absorbing resin; b) mixing the base resin and the curing agent at 60-75° C. to obtain a coarse mixed resin; then refining and fine mixing the coarse mixed wave-transmitting resin at 65-75° C. to obtain a fine mixed wave-transmitting resin; c) coating the finely mixed absorbing resin obtained in step a) on release paper at a coating temperature of 75° C. to 95° C. to obtain an absorbing adhesive film; coating the finely mixed transparent resin obtained in step b) on release paper at a coating temperature of 75° C. to 95° C. to obtain a transparent adhesive film; d) compounding the fiber fabric between two layers of the wave-transmitting adhesive film at a compounding temperature of 65 to 85° C. to obtain a primary pre-impregnated fabric, and then curing the primary pre-impregnated fabric at 70 to 90° C. to obtain a pre-impregnated fabric; e) Compounding the preimpregnated fabric between two layers of the absorbing adhesive film at a compounding temperature of 65° C. to 80° C. to obtain an absorbing prepreg, wherein the absorbing prepreg comprises, from top to bottom, the absorbing adhesive film, the transparent adhesive film, the fiber fabric, the transparent adhesive film and the absorbing adhesive film.
4. The method according to claim 4, characterized in that In step a), the mass ratio of the absorbent, the matrix resin and the curing agent is 5-13.5:3-4:0-1.
5. The method according to claim 4, characterized in that In step b), the mass ratio of the base resin to the curing agent is 3 to 4:
1.
6. The method of claim 4, characterized in that The absorbent is one of flaky carbonyl iron, flaky sendust, flaky iron silicon chromium, flaky iron silicon nickel and chopped carbon fiber or any combination thereof, and the particle size of the absorbent is 5 to 100 microns.
7. The method of claim 4, characterized in that The base resin is one of epoxy resin, cyanate resin, bismaleimide resin and phenolic resin or any combination thereof; the curing agent is one of dicyandiamide, diallyl bisphenol A, phthalic anhydride, p-phenylenediamine and p-toluenesulfonic acid or any combination thereof.
8. The method of claim 4, characterized in that The fiber fabric is a mixed fabric of one of quartz fiber fabric, aramid fiber fabric and basalt fiber fabric or any combination thereof, and the thickness of the fiber fabric is 0.05-0.1 mm.
9. The method of claim 4, characterized in that The thickness of the wave-transmitting adhesive film is 40% to 60% of the thickness of the fiber fabric; the thickness of the wave-absorbing adhesive film is 120% to 166.7% of the thickness of the fiber fabric.
10. Use of the microwave absorbing prepreg according to any one of claims 1 to 2 and the microwave absorbing prepreg prepared by the method according to any one of claims 3 to 9 in microwave absorbing equipment.
Citation Information
Patent Citations
A microwave-absorbing cyanate resin, a microwave-absorbing cyanate resin composite and its preparation method
CN113755013B
A microwave-absorbing epoxy resin, a microwave-absorbing epoxy resin composite and its preparation method
CN113801437B
Wave-absorbing adhesive film material and preparation method thereof
CN112029421A
Preparation method of low-frequency wave-absorbing prepreg for P and L wave bands
CN118744542A
Preparation method of wave-transparent fiber for reducing curing deformation of co-curing composite material
CN118769565A
Cited By
Preparation method of high-temperature-resistant wave-absorbing composite material
CN121086305A